(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Since the establishment of the International GNSS Service (IGS) stations, they have been used as control stations for assigning the Precise point positioning (PPP) positions using one Global Navigation Satellite System (GNSS) receiver, which has increased from day-to-day. There are some factors affecting the accuracy of PPP positioning. This research aims to investigate the relation between the IGS distance and observed field points as well as to attempt to describe that relation mathematically/statically. For the realization of that aim, two field points are fixed inside the Assiut University campus and observed successively for a session of 24 hour observation. The position of each field point is assigned with the help of each one of the available IGS station products. It must be known that these products are found after observations in three files (IGU, IGR, and final IGS), whereas IGU is used directly as real-time data (ultra-rapid), IGR (rapid) is used through (17-41 hours) after observation, and (final IGS) used after 12 – 18 days. Coordinates and point errors of each field points are computed and represented. It has been found that the errors have a positive relation with the available IGS stations distances. The relation between these distances and point positioning errors have been represented and described according to a model. The accuracy of the presented model is (R ≅ .98, x2 ≅ 2.5 × 10-3).